2014
DOI: 10.5155/eurjchem.5.3.497-502.1080
|View full text |Cite
|
Sign up to set email alerts
|

A validated stability indicating HPLC method for determination of sitagliptin

Abstract: A comparative and stability-indicating reversed phase high performance liquid chromatographic study have been developed and validated for sitagliptin phosphate. The liquid chromatographic determination was achieved isocratically on Poroshell 120 EC-C18 (100 × 4.6 mm, i.d.; particle size, 2.7 µm), Pursuit 5PFP (150 × 4.6 mm, i.d.; particle size, 5 µm) and Chromolith performance RP-18e (100 × 4.6 mm, i.d.; macropore diameter, 2 µm) columns using a mobile phase consisting of methanol:water:triethylamine:acetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Therefore, very sensitive analytical approaches are required to detect and identify very low levels of these impurities. In the literature, various methods are reported for the analysis of sitagliptin drug substances and drug products including the SFC-MS/MS [ 14 ], RP-HPLC [ 15 , 16 ], HPTLC [ 17 ], HPLC [ 18 , 19 , 20 , 21 ], HPLC-CD [ 22 ], LC-UV, LC-MS, and FT-IR method [ 23 ], as well as the UV spectrophotometric [ 24 ] and UPLC-MS/MS [ 25 ] method; however, these are not sophisticated enough to analyze a particular 7-nitroso impurity. A review of the literature revealed that there is no specific method available for the analysis of 7-nitroso impurity in sitagliptin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, very sensitive analytical approaches are required to detect and identify very low levels of these impurities. In the literature, various methods are reported for the analysis of sitagliptin drug substances and drug products including the SFC-MS/MS [ 14 ], RP-HPLC [ 15 , 16 ], HPTLC [ 17 ], HPLC [ 18 , 19 , 20 , 21 ], HPLC-CD [ 22 ], LC-UV, LC-MS, and FT-IR method [ 23 ], as well as the UV spectrophotometric [ 24 ] and UPLC-MS/MS [ 25 ] method; however, these are not sophisticated enough to analyze a particular 7-nitroso impurity. A review of the literature revealed that there is no specific method available for the analysis of 7-nitroso impurity in sitagliptin.…”
Section: Introductionmentioning
confidence: 99%